1995
DOI: 10.1161/01.res.77.5.984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NO Modulation on Cardiac Arrhythmias in the Rat Isolated Heart

Abstract: It has been proposed that NO may function as an endogenous cardioprotectant. We have investigated whether modulation of NO levels (detected in coronary effluent by chemiluminescence) by a blocker of its synthesis, by supplementation of its precursor, and by administration of an NO donor can influence reperfusion arrhythmias in the isolated rat heart. Rat hearts were perfused with modified Krebs' solution and subjected to 5, 35, or 60 minutes of left regional ischemia followed by 10 minutes of reperfusion. NG-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
1
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 46 publications
8
70
1
2
Order By: Relevance
“…This increase in coronary vascular resistance can be directly attributed to the inhibition of NOS activity and the subsequent impairment of ⅐ NO-induced vasorelaxation, as was described previously in a similar model (Pabla and Curtis, 1995). During L-NAME administration, the progressive decrease in RPP might be related to the impairment of oxygen and substrate supplies due to vasoconstriction.…”
Section: Tablesupporting
confidence: 72%
“…This increase in coronary vascular resistance can be directly attributed to the inhibition of NOS activity and the subsequent impairment of ⅐ NO-induced vasorelaxation, as was described previously in a similar model (Pabla and Curtis, 1995). During L-NAME administration, the progressive decrease in RPP might be related to the impairment of oxygen and substrate supplies due to vasoconstriction.…”
Section: Tablesupporting
confidence: 72%
“…We have described premature death in NOS1-and NOS1/NOS3 Ϫ/Ϫ -deficient mice (39) and recently, in a model of myocardial infarction, that the survival is dramatically decreased in NOS1 Ϫ/Ϫ mice (40). Interestingly, it has been described that pharmacological blockade of NOS1 increases ventricular fibrillation in models of ischemia-reperfusion, in a manner that is reversed by NO donors (41)(42)(43).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, Pabla and Curtis (25) showed that endogenous NO does not appear to facilitate early recovery from systolic and diastolic stunning as a result of any direct action on the myocardium. The role of NO in ischemia/reperfusion appears to be dependent on the time of ischemia (26), being more significant with longer periods of coronary occlusion (>35 min). One may argue that L-NAME had no effect because it was washed out from the isolated heart.…”
Section: Discussionmentioning
confidence: 99%